Becoming an interprofessional practitioner: factors promoting the application of pre-qualification learning to professional practice in maternity care. Issue 1 (January 2014) - Murray-Davis, Beth; Marshall, Michelle; Gordon, Frances
Abstract Teamwork and collaboration have been recognized as essential competencies for health care providers in the field of maternity care. Health care policy and regulatory bodies have stressed the importance of Interprofessional Education (IPE) for learners in this field; however, there is little evidence of sustained application of pre-qualifying IPE to the realm of interprofessional collaboration (IPC) in practice following qualification. The aim of this research was to understand how newly qualified midwives applied their IPE training to professional practice. A purposive sample of midwifery students, educators, new midwives and Heads of Midwifery from four universities in the United Kingdom participated in semi-structured interviews, questionnaires and focus groups. Qualitative, grounded theory methodology was used to develop the emerging theory. Newly qualified midwives appeared better able to integrate their IPE training into practice when IPE occurred in a favourable learning environment that facilitated acquisition and application of IPE skills and that recognized the importance of shared partnership between the university and the clinical workplace.